The effect of JGP slab on the stability of deep excavation - Chan, Siew Long (2015)
In this project, two-dimensional simulations via software PLAXIS 2D were carried out using finite element method, to evaluate the performance of jet grouted piles during a deep excavation. The thickness and arrangement of the jet grouted slabs will be varied while maintaining the depth and width of excavation. Analyses were carried out in soils containing undrained (c) clays of different shear strength, cu and Young’s modulus, E to investigate the effects of JGP has on them. Important parameters such as maximum wall displacement, maximum wall bending moment, maximum soil displacement, strut forces and factor of safety (strength reduction factor) during the last phase of excavation were used as basis of comparison to evaluate the performance of the JGP on deep excavations. Lower maximum wall displacement, bending moment, soil displacement and strut forces are deemed to be more favourable while lower factor of safety is considered unfavourable. This study has revealed that the arrangement of the JGP is the most effective when located directly beneath the base of excavation and the efficiency of the JGP installation will be considered through the assessment of the percentage improvement on the result parameters upon increasing thickness of the JGP.